Chronicles of a Radical Hag (with Recipes) : A Novel - Landvik, Lorna, 1954- (Book collections on Project MUSE., 2019)
"In the small town of Granite Creek, Minnesota, Haze Evans suffers a stroke at the age of 89 and slips into a coma. Haze is a local legend, having written a daily column in the Granite Creek Gazette for fifty years running"--